ChemInform Abstract: Critical Properties of Cu6Sn5 in Electronic Devices: Recent Progress and a Review. Issue 19 (April 2016) - Mu, D. K.; McDonald, S. D.; Read, J.; Huang, H.; Nogita, K.
Abstract: Review: 189 refs.